2009
DOI: 10.1007/s00436-009-1410-4
|View full text |Cite
|
Sign up to set email alerts
|

An appraisal of current and new techniques intended to protect bulls against Culicoides and other haematophagous nematocera: the case of Schmergow, Brandenburg, Germany

Abstract: The outbreak of bluetongue (BTV-8) in many parts of north-western Europe led to efforts to curb the spread of the disease, particularly in farms with valuable livestock, as on a stud bull farm in Schmergow, Brandenburg, Germany. In the abundance of the putative BT vectors, Palaearctic Culicoides species, several vector control methods were applied in the hope for a reduction of the target insect populations. Insecticide-impregnated ear tags and regular treatments at 6-week intervals of all bulls with deltameth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 13 publications
1
25
0
Order By: Relevance
“…The detailed results of the monitoring in the different German regions are presented in the ten papers following this introducing overview in the present volume of the journal Kiehl et al 2009;Vorsprach et al 2009;Balczun et al 2009;Kiel et al 2009; Clausen Bartsch et al 2009;Stephan et al 2009;Bauer et al 2009;Hörbrand and Geier 2009). However, the common features can be summarized as follows:…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The detailed results of the monitoring in the different German regions are presented in the ten papers following this introducing overview in the present volume of the journal Kiehl et al 2009;Vorsprach et al 2009;Balczun et al 2009;Kiel et al 2009; Clausen Bartsch et al 2009;Stephan et al 2009;Bauer et al 2009;Hörbrand and Geier 2009). However, the common features can be summarized as follows:…”
Section: Resultsmentioning
confidence: 99%
“…The 10 papers following this introducing overview in the present volume of the journal Vorsprach et al 2009;Balczun et al 2009;Kiel et al 2009;Kiehl et al 2009;Bartsch et al 2009;Clausen et al 2009;Stephan et al 2009;Bauer et al 2009;Hörbrand and Geier 2009) describe the results obtained during this monitoring program, which ran from the end of March 2007 until the end of May 2008.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Although not studied in detail, Culicoides species in temperate climate zones are expected to hibernate in a late larval stage (Szadziewsi et al 1997). Moreover, vector surveillance studies in Northern Europe indicated very low but regular activity of adult Culicoides also in winter (Losson et al 2007;Bauer et al 2009;Clausen et al 2009;Hoffmann et al 2009;Kiel et al 2009;Mehlhorn et al 2009). These findings raised a discussion whether or not these individuals represent an overwintering adult population or newly emerged imagines (Losson et al 2007).…”
Section: Short Communicationmentioning
confidence: 94%
“…The treatment of livestock and animal housing with pyrethroid insecticide combined with the use of midge-proofed housing for viraemic or high-value animals and reduction of local breeding sites are the best options currently available (Carpenter et al 2008). However, application of pour-on insecticides has been unsuccessful with no noticeable reduction in the density of biting midges in highly-challenged areas (Bauer et al 2009). Control of midges is unlikely to be effective given that they are extremely widespread, and appear to be very effective at spreading SBV.…”
Section: Prevention and Controlmentioning
confidence: 99%